(untitled) (Indian Journal of Public Health Research & Development, 2020)
Aim: To evaluate and compare the flexural properties of three commercially available brands of PMMA heat cure denture base resins after water immersion over a period of 3 months. Method and Material: Commercially available heat cure denture base resins (DPI, Triplex, and Trevalon) were used in the study. An aluminum die was fabricated according to ISO 1567. Each of the tested materials was manipulated according to manufacturer’s instructions. Total of 60 samples were made (n=10). With 3 control (dry) groups and three experimental (water immersed) groups. The samples were subjected to INSTRON universal testing machine. Statistical Analysis Used: Student ‘t’ test, ANOVA and Post hoc tukey’s test. Results: Student ‘t’ test indicated that there is significant difference in the flexural properties of the denture base resins after long term water immersion with p<0.05 for all the three groups. ANOVA indicated that there was no significant difference among the three groups/brands. Conclusions: The flexural properties of heat cure denture base resins was affected by long term water immersion. The ultimate flexural strength decreased, flexural strength at proportional limit remained same and modulus of elasticity decreased. Thus after long term water immersion, the denture base material becomes weaker and stiffer.